KESIAPAN GURU MATEMATIKA MTS IMPLEMENTASIKAN KURIKULUM BERBASIS CINTA - Erna Sari Agusta; Anang Setiawan (Jurnal Lingkar Mutu Pendidikan, 2026)
The implementation of the Love-Based Curriculum (KBC) requires mathematics teachers to be prepared to adjust the planning, implementation, and evaluation of learning. This study aims to describe the readiness of mathematics teachers in implementing the KBC. This study uses a qualitative approach with a descriptive type through a survey method. The research subjects were mathematics teachers of MTs in DKI Jakarta Province who were selected purposively. Data collection was carried out through closed questionnaires, interviews, and documentation. Data analysis included data reduction, data presentation, and drawing conclusions. Data validity was carried out by triangulation of sources. The level of readiness was divided into three categories, namely ready (76–100), quite ready (51-75), lack ready(26–50), and not ready (≤25). The results showed that 62.5% of teachers did not understand the concept and objectives of the Love-Based Curriculum, 50% of teachers still had difficulties in preparing teaching modules or lesson plans, 43.75% of teachers had not implemented value- and character-based learning, and 37.5% of teachers had not implemented value- and character-based diagnostic and formative assessments. Therefore, mathematics teachers' readiness to implement the Love-Based Curriculum still requires continuous improvement. Interviews revealed obstacles such as limited training, uneven conceptual understanding, and adaptation to changing learning paradigms. Therefore, ongoing efforts through training, mentoring, and strengthening the professional competencies of mathematics teachers are needed to ensure optimal implementation of the Love-Based Curriculum.